What a solution of the equation -8x + 13 = -19
9 answers
The solution to the equation -8x + 13 = -19 is x = 4.
What is a solution of the equation 11 - 4x = -9
The solution to the equation 11 - 4x = -9 is x = 5.
What is the solution for the equation 2/5 x + 4 = 1/5
To solve the equation 2/5 x + 4 = 1/5, we need to isolate x on one side of the equation.
Subtract 4 from both sides:
2/5 x = 1/5 - 4
Simplify:
2/5 x = 1/5 - 20/5
Combining fractions:
2/5 x = -19/5
Multiply both sides by the reciprocal of 2/5, which is 5/2:
(5/2)(2/5) x = (5/2)(-19/5)
Simplify:
1x = -19/2
The solution to the equation is x = -19/2.
Subtract 4 from both sides:
2/5 x = 1/5 - 4
Simplify:
2/5 x = 1/5 - 20/5
Combining fractions:
2/5 x = -19/5
Multiply both sides by the reciprocal of 2/5, which is 5/2:
(5/2)(2/5) x = (5/2)(-19/5)
Simplify:
1x = -19/2
The solution to the equation is x = -19/2.
What is the solution of the equation 5/3-2x=1/6
To solve the equation 5/3 - 2x = 1/6, we need to isolate x on one side of the equation.
Subtract 5/3 from both sides:
5/3 - 2x - 5/3 = 1/6 - 5/3
Simplify:
-2x = 1/6 - 5/3
Find a common denominator:
-2x = 1/6 - 10/6
Combine fractions:
-2x = -9/6
Simplify:
-2x = -3/2
Divide both sides by -2:
(-2x)/(-2) = (-3/2)/(-2)
Simplify:
x = 3/4
The solution to the equation is x = 3/4.
Subtract 5/3 from both sides:
5/3 - 2x - 5/3 = 1/6 - 5/3
Simplify:
-2x = 1/6 - 5/3
Find a common denominator:
-2x = 1/6 - 10/6
Combine fractions:
-2x = -9/6
Simplify:
-2x = -3/2
Divide both sides by -2:
(-2x)/(-2) = (-3/2)/(-2)
Simplify:
x = 3/4
The solution to the equation is x = 3/4.
What is the solution of the equation 0.2x-2.15=-8.27
To solve the equation 0.2x - 2.15 = -8.27, we need to isolate x on one side of the equation.
Add 2.15 to both sides:
0.2x - 2.15 + 2.15 = -8.27 + 2.15
Simplify:
0.2x = -6.12
Divide both sides by 0.2:
(0.2x) / 0.2 = (-6.12) / 0.2
Simplify:
x = -30.6
The solution to the equation is x = -30.6.
Add 2.15 to both sides:
0.2x - 2.15 + 2.15 = -8.27 + 2.15
Simplify:
0.2x = -6.12
Divide both sides by 0.2:
(0.2x) / 0.2 = (-6.12) / 0.2
Simplify:
x = -30.6
The solution to the equation is x = -30.6.